mRNA in situ hybridization analysis of VEGF in chronic lymphocytic leukemia - Jaafar, Abdulkareem M.; Abdul Majeed, Ban A.; Al-Rubaie, Haythem A. MJ (Journal of the Faculty of Medicine Baghdad, 2011)
Background: Several factors render chronic lymphocytic leukemia (CLL) an interesting subject for study by researchers. These include marked progress in understanding the molecular biology of normal and neoplastic lymphocytes and recent advances in molecular genetics techniques. Among molecular markers, vascular endothelial growth factor (VEGF), have been widely studied.Objective: The aim of the study is to evaluate the role of VEGF in the pathogenesis of CLL and its role in disease progression.Patients, materials and methods: A retrospective cross-sectional study was done on 60 patients with chronic lymphocytic leukemia (45 males & 15 females) compared with 20 controls (anemic patients), all recruited at the Medical City Hospital/ Teaching Laboratories/ Baghdad from January 2004 to December 2007. The bone marrow biopsy of each was re-examined histologically. In situ hybridization was performed utilizing biotin labeled VEGF cDNA probes.Results: The frequency of VEGF positivity was 95% (57 of 60 cases). A statistically significant inverse correlation was found between increasing VEGF scores and lower packed cell volume level and lower platelet count. A statistically significant association was found between advanced modified Rai stage and patients with high score. In addition, there was a statistically significant positive correlation between increasing scores of VEGF and advancing clinical stage. Conclusions: The score of VEGF is high among patients with advanced clinical stage of the disease.